HOW TO ADAPT PHYSICAL EXERCISES TO AQUAGYM PROGRAMS FOR WOMEN AGED 25-35 YEARS - Boris Râsneac; Sorin Raţă; Alexandra Plesciuc (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
This paper has presented a program of four water exercises for improving health to women aged 25-35 years. The results obtained allow effective establishment of the program subsequently developed which can be applied in the physical education to adults.